P‐1.7: Influence of Mg Content and Argon/Oxygen Ratio on Photoelectric properties of co‐sputtering MIZO. (28th November 2018) - Yang, Yukun; Lu, Huiling; Zhang, Shengdong
Abstract : The authors investigated optical and electrical properties of MIZO film which was prepared by co‐sputtering for the first time. MgO and IZO (In:Zn=9:1) were used as the two targets to sputter at the same time. By controlling the sputtering power of the two targets, the content of Mg, resistivity and the optical band gap of MIZO can be adjusted, thereby meeting the needs of the applications of UV detector and other purposes. With the increasing of Mg content, the resistivity of MIZO increased from 9.1× 10 −4 Ωcm to 6.0 × 10 8 Ωcm, and the band gap could be broadened to 3.97eV. Except for Mg content, the effect of the ratio of argon to oxygen was also explored, IZO as one of the two targets is very sensitive to the ratio of argon to oxygen, leading to the decrease of the MIZO resistivity of the same magnesium content with the increase of the ratio of argon to oxygen, while the band gap increases first and then decrease.